Strategi Pemberdayaan Petani Kelapa di Desa Selumbung Kecamatan Manggis Kabupaten Karangasem (Jurnal Agribisnis dan Agrowisata, 2026)
Coconut Farmer Empowerment Strategy in Selumbung Village, Manggis District, Karangasem Regency. Selumbung Village has an area of 665,225 hectares with a topography of plains and hills and is located ± 4 km from the center of the Manggis District Government.  Selumbung Village has abundant potential resources for farming rice fields, fields, hills and coconut plantations.  Selumbung Village is one of the coconut producing villages in Manggis District, Karangasem Regency. Selumbung Village has a fairly good coconut commodity. The purpose of this study was to identify internal and external factors, to formulate alternatives and to determine the right strategy for empowering coconut farmers in Selumbung Village, Manggis District, Karangasem Regency. The results showed that the internal factor that became the strength was that the Selumbung Village coconut fruit had better fruit than the fruit in the surrounding area.  While the weakness is that coconut processing is not optimal in Selumbung Village so that the selling power is still low.  Then from external factors that become opportunities is a wide market share in various regions.  While the threat consists of not much capital owned by coconut farmers in developing their business. The Coconut Farmer Empowerment Strategy in Selumbung Village was obtained from the results of the SWOT Matrix.
Keywords: potential; coconut; strategy; farmer empowerment